Longivitas post ekuilibrasi spermatozoa sapi crossbreed Ongole menggunakan bahan pengencer yang disuplementasi Ekstrak buah merah - Nurcholis, Nurcholis; Salamony, S M; Irianto, Apri (AGRICOLA, 2021)
The use of Papuan red fruit as a supplementation ingredient in diluents is one solution to the high price of diluent raw materials. The purpose of this study was to determine the effect of using a diluent supplemented with red fruit extract (RFE) in various levels on the quality of liquid semen of Ongle crossbred cattle during storage at equilibration temperature. The research was conducted in the Animal Health Laboratory of Semangga District and the Independent Laboratory. The research method and design used were a completely randomized design (CRD) with 4 treatments and 5 replications. This study used 4 diluting treatments, namely P0 = Tris egg yolk (TKT), P1 = (TKT + 0.1 ml RFE), P2 = (TKT + 0.3 ml RFE) and P3 = (TKT + 0.5 ml RFE). Semen was collected using an artificial vagina, immediately after the semen storage was evaluated macroscopically and microscopically. The homogenized semen was divided into 4 tubes, then put the semen into the straw as much as 0.25 ml. The next process is equilibration at 5oC for 2, 4, 6, 8 hours and evaluation of spermatozoa longivity is carried out at pots equilibration. The results showed that there was a difference (P <0.05) in the longivity of spermatozoa in P3 treatment against the control. In conclusion, it can be concluded that the red fruit extract supplementation in egg yolk tris diluent was able to maintain spermatozoa longevity.